The type specimens of Calyptratae (Diptera) housed in non-traditional institutions in Argentina - Patitucci, Luciano D. (2015)
Fil: Patitucci, Luciano Damián. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.